Medial swivel dislocation of talonavicular joint due to low energy trauma - Nair, Syam Gangadharan; Nair, Sudheesh Vasanthakumari Sreeramakrishnan; Joseph, Sachin; Surendran, Arun Chand (International Journal of Research in Orthopaedics, 2020)
Medial swivel variant of talonavicular dislocation is rare. Usually, it is caused by high velocity trauma. They are relatively easier to reduce and are associated with fewer complications than pure dorsal dislocations and sub talar dislocations. We report a case of medial swivel dislocation of talonavicular caused by a low energy trauma, its management and one year follow up result.